Age‐stratified cut‐off points for the nocturnal penile tumescence measurement using Nocturnal Electrobioimpedance Volumetric Assessment (NEVA®) in sexually active healthy men. (25th October 2015) - Tok, A.; Eminaga, O.; Burghaus, L.; Herden, J.; Akbarov, I.; Engelmann, U.; Wille, S.
Summary: The current nocturnal penile tumescence (NPT) measurement is based on standard cut‐off levels defined regardless of age. This study was conducted to provide age‐stratified cut‐off points for NPT measurement. Forty sexually active healthy men between 20 and 60 years old were enrolled and divided equally into four groups defined by age (20–29, 30–39, 40–49 and 50–60 years.). None of the candidates had sexual dysfunction or sleep disturbance or used supportive medication to enhance sexual function. Erectile function was evaluated by using the 5‐item version of the international index of erectile function (IIEF‐5). NPT was observed using the nocturnal electrobioimpedance volumetric assessment (NEVA ® ). The NPT values of healthy men aged 20–60 years varied from 268.7% to 202.3%. The NPT differed significantly between age groups ( P  < 0.0009); however, no significant differences between men aged 30–39 and 40–49 ( P  = 0.593) were observed. Age was weakly associated with IIEF‐5 scores ( P  = 0.004), whereas a strong and negative correlation between age and NPT ( P  < 0.0001) was found. IEF‐5 scores were not significantly associated with NPT ( P  = 0.95). Therefore, the standard values for NPT testing should be considered in the evaluation of the nocturnal penile activity of men of all ages.